Generalized hybrid mappings on [InlineEquation not available: see fulltext.] spaces - Bancha Nanjaras (2018)
© 2014, Nanjaras and Panyanak; licensee Springer. In this paper, we obtain the demiclosed principle, fixed point theorems, and Δ-convergence theorems for the class of generalized hybrid mappings on [InlineEquation not available: see fulltext.] spaces with [InlineEquation not available: see fulltext.]. Our results extend the results of Lin et al. (Fixed Point Theory Appl. 2011:49, 2011) and many others.